1998
DOI: 10.1172/jci2676
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive properties of methotrexate: apoptosis and clonal deletion of activated peripheral T cells.

Abstract: The folate antagonist methotrexate (MTX) is extensively used in graft-versus-host disease, rheumatoid arthritis, and other chronic inflammatory disorders. In addition to its antiinflammatory activity associated with increased release of adenosine, MTX exerts antiproliferative properties by inhibition of dihydrofolate reductase and other folate-dependent enzymes. However, the mechanisms of immunosuppressive properties associated with low-dose MTX treatments are still elusive. We report here that MTX (0.1-10 M) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
266
3
9

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(302 citation statements)
references
References 38 publications
17
266
3
9
Order By: Relevance
“…Mice which were primed with minor antigen incompatible spleen cells and simultaneously treated with CP showed clonal deletion of activated allogeneic T cells in the periphery and the thymus [43,44]. Interestingly, we found that CP induced apoptosis in activated as well as in resting T cell populations, while MTX only mediated apoptosis of activated T cells, as described previously [22].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Mice which were primed with minor antigen incompatible spleen cells and simultaneously treated with CP showed clonal deletion of activated allogeneic T cells in the periphery and the thymus [43,44]. Interestingly, we found that CP induced apoptosis in activated as well as in resting T cell populations, while MTX only mediated apoptosis of activated T cells, as described previously [22].…”
Section: Discussionsupporting
confidence: 83%
“…Glucocorticoids have been shown to induce apoptosis of murine thymocytes [17], T cell hybridomas [18] and human leukaemic T cells [19]. Although methotrexate (MTX) was found to trigger CD95L expression in leukaemic T cell lines [20] and hepatoma cell lines [21], MTX may also induce apoptosis by a CD95-independent pathway [22]. Induction of CD95-dependent apoptosis by cyclophosphamide has been described for in vivo treatment of rat thymocytes [23].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described that nucleotide restriction inhibits T cell proliferation and could induce apoptosis of cycling T cells in vitro (7,8,27). Therefore, we investigated the effects of nucleotide synthesis inhibitors on T cell proliferation in vivo.…”
Section: Nucleotide Synthesis Inhibitors Affect Peptide-induced Prolimentioning
confidence: 99%
“…We and other investigators showed that the immunosuppressive effects of the Western antirheumatic drug (ARD), HCQ, and of Chinese ARDs, tetrandrine (Tet) and Tripterygium wilfordii hook F (TWHf), were mediated through both the inhibition of T cell activation and the induction of T cell apoptosis (12)(13)(14)(15). In addition, high concentrations (0.1-10 M) of MTX, another important DMARD, have been shown to induce apoptosis of activated PBLs (16).…”
mentioning
confidence: 99%